2010
DOI: 10.1007/s11069-010-9521-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physical parameterization schemes on numerical simulation of super cyclone Gonu

Abstract: The objective of this study is to investigate in detail the sensitivity of cumulus, planetary boundary layer and explicit cloud microphysics parameterization schemes on intensity and track forecast of super cyclone Gonu (2007) using the Pennsylvania State University-National Center for Atmospheric Research Fifth-Generation Mesoscale Model (MM5). Three sets of sensitivity experiments (totally 11 experiments) are conducted to examine the impact of each of the aforementioned parameterization schemes on the storm'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Dynamics and physical processes are very important in numerical models for understanding and forecast of TC [9]. Reference [10] revealed the sensitivity of TC development to cloud microphysics schemes in a hydrostatic model.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamics and physical processes are very important in numerical models for understanding and forecast of TC [9]. Reference [10] revealed the sensitivity of TC development to cloud microphysics schemes in a hydrostatic model.…”
Section: Introductionmentioning
confidence: 99%
“…(e.g. Mohanty et al, 2004;Bhaskar Rao et al, 2006, 2007Prasad and Rama Rao, 2003;Trivedi et al, 2006;Srinivas et al, 2007Srinivas et al, , 2010Deshpande et al, 2010;Krishna et al, 2010;Mukhopadhyay et al, 2011;Singh et al, 2008Singh et al, , 2011Singh et al, , 2012Pattanik andMohanty, 2008, 2010;Raju et al, 2011a). Very few studies have reported the performance of numerical models statistically for the cyclones over the NIO.…”
Section: Introductionmentioning
confidence: 99%
“…Mandal et al (2004) studied the impact of various physical parameterization schemes on the prediction of two tropical cyclones formed during November 1995 over the Bay of Bengal using MM5. Deshpande et al (2010) studied the sensitivity of various physical parameterization schemes on the numerical simulation of Super Cyclone Gonu and reported that the forecast track and intensity of the cyclone are most sensitive to CPS, compared to other physical parameterization schemes (e.g. PBL and MPS).…”
Section: Introductionmentioning
confidence: 99%